Peningkatan Efektivitas Sistem IPAL Lumpur Aktif dalam Menurunkan Nilai BOD (Inlet- Outlet) PT Rubberhock Lie, Sunggal (2025) - Tarigan, Usaha Satria Pratama (INSTITUT KESEHATAN DELI HUSADA, 2025)
Rubber industry wastewater has the potential to pollute the environment due to its high Biochemical Oxygen Demand (BOD) levels, which often exceed quality standards. This condition affects water quality and poses risks to the health of surrounding communities. Therefore, appropriate wastewater treatment technology is required. This community service program aims to improve the effectiveness of the wastewater treatment plant (WWTP) with the activated sludge process in reducing BOD levels from the inlet to the outlet at PT Rubberhock Lie, Sunggal . The program is expected to have positive impacts, including strengthening the industry’s capacity in wastewater management, protecting the surrounding environment, and contributing to sustainable development.